Pengelolaan Limbah Ternak Sapi Menjadi Pupuk Organik Komersial di Dusun Kalipucang, Bangunjiwo, Bantul, Yogyakarta - Sukamta, Sukamta; Shomad, Muhammad Abdus; Wisnujati, Andika (Berdikari: Jurnal Inovasi dan Penerapan Ipteks, 2017)
The effort to make cow dung has significant added value is the main purpose of this community service activity. The fact is still not much effort to increase the added value of cow dung such as making cow dung into organic fertilizer products with commercial value. Besides, this activity also aims to create a healthy community environment and provide an impact of economic improvement of local communities. Method of implementation of activity begins with observation and mapping area, socialization, implementation, analysis and evaluation, and improvement. The observations were conducted to review the Kalipucang Hamlet area as a whole, interviewing with all components of the community, such as village apparatus and villagers or viewing the field conditions directly as well as doing this mapping to clarify the situation and characteristics of Kalipucang Hamlet related to livestock and land, then socialized to the head of RT, Chairman of the RW, and the local village chief and community. Socialization also serves to explore more deeply about the problems experienced by the community and the solutions needed, so as to provide an output that is in accordance with the wishes and needs of the community. The location of the implementation of this program is in the cattle field of the group Andini Makmur, Kalipucang Hamlet, Bangunjiwo, Bantul, DIY. The series of activities of community service programs that will be carried out include several stages : organic fertilizer material delivery, construction of fertilizer production site, livestock collection, organic fertilizer practice, organic fertilizer monitoring, organic fertilizer cooperative system, launching and evaluation and mentoring. From this activity produced organic fertilizer and successfully established a cooperative that manages the process of making organic fertilizer, packing, until the commercialization. From this activity obtained significant added value in economic aspect as well as from the side of public health because no longer there is pollution from cow dung d neighborhood of residence.Â Keyword : Cow dung, organic fertilizer, community service, marketing.